2013
DOI: 10.1007/s11999-012-2765-x
|View full text |Cite
|
Sign up to set email alerts
|

Unstable SCFE: Review of Treatment Modalities and Prevalence of Osteonecrosis

Abstract: Background The treatment of unstable slipped capital femoral epiphysis (SCFE) is rapidly evolving with the ability to correct epiphyseal alignment using the modified Dunn technique. Adopting a new treatment method depends on confirming that it achieves its goals, produces few, nonserious complications with no lasting sequelae, and improves the natural history of the disorder compared with known treatment methods. As such, the rates of osteonecrosis and complications after current treatments of unstable SCFE mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
1
8

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 21 publications
2
62
1
8
Order By: Relevance
“…Second, our cohort represents the learning curve of the three surgeons. Thus, the overall proportion of patients who developed osteonecrosis may be higher than the expected proportion reported by the originators of the technique [13,14,29]. However, all surgeons were experienced in the surgical dislocation approach and the proportion of osteonecrosis in this series compares well to other recent studies [24,25].…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…Second, our cohort represents the learning curve of the three surgeons. Thus, the overall proportion of patients who developed osteonecrosis may be higher than the expected proportion reported by the originators of the technique [13,14,29]. However, all surgeons were experienced in the surgical dislocation approach and the proportion of osteonecrosis in this series compares well to other recent studies [24,25].…”
Section: Discussionsupporting
confidence: 48%
“…The increased attention is most likely related to the fact that osteonecrosis of the femoral head was not reported in the first descriptive studies [13,14,29]. Recent studies, however, have reported that approximately 25% of patients undergoing a modified Dunn for unstable SCFE developed osteonecrosis [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of AVN in SCFE varies in literature from 5% to 47%. 1 Zaltz et al 23 made a literature review and found a cumulative rate of osteonecrosis of 23.9% among patients with SCFE classified as unstable. In our study, we had three osteonecrosis on nine unstable hips compared to ten stable hips without any case of AVN.…”
Section: Discussionmentioning
confidence: 99%